QUANTITATIVE STUDIES ON THE VEGETATION OF ISLAMABAD (Biological Sciences - PJSIR, 2001)
Quantitative studies on the vegetation of Islamabad were conducted during spring-summer, 1998. Phytosociological observations were made and 17 plant communities were recognized in the area on the basis of highest importance value. Acacia modesta Wall. was the dominant tree of the study area, occurring as first dominant in 6 out of 17 stands, followed by Broussonetia papyrifera Vent. (first dominant in 3 stands), and Dalbergia sissoo Roxb.(first dominant in 2 stands). Justicia adhatoda L. was the dominant shrub (first dominant in 3 stands). It was observed that the original natural and xerophytic vegetation in the central areas has been changed into mesophytic type due to large-scale cultivation of trees.